Biological Review of Squid (Stenoteuthis oualaniensis) in North Sulawesi (Case Study of Squid Caught in Motto Waters, North Lembeh, Bitung City) - Arifin, Muhammad Zainul; Saranga, Rudi; Hamel, Samuel; Manohas, Jul; Putri, Elsari T.; Antou , Lusje (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
Fishing with the target of squid by fishermen in the Motto Village is a hereditary cultural fishing and has been going on for a long time. The research on squid’s biology of Motto village is important to support this fishing activities The purpose of this study was to identify squid caught based on biology in the waters of the Motto Village. The method used in this research is descriptive research method. The research was conducted during September to November 2021. Data was collected through observation and interviews. The results obtained indicated that the squids caught in Motto waters were a Stenoteuthis oualaniensis. Maximum mantle length 23 cmML, minimum mantle length 9.6 cmML with an average of 11.80 cm ML. Maximum weight of 500 grams, minimum weight of 10 grams with an average of 70 grams. The results of the length-weight ratio obtained the value of R2 was 0.7929 where the determination or effect of the length variation of the mantle on the weight variation of the squid was 79.29%. The growth pattern of squid are negative allometric or length increase more dominant than weight increase.